Strategic multilateral exchange : general equilibrium with imperfect competition - Gabszewicz, Jean Jaskold (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2002)
Aimed at both undergraduate and postgraduate students, this text on strategic multilateral exchange offers comprehensive cover on economic equilibrium and imperfect competition.
Includes bibliographical references (p. 207-212) and index.
oif 04/05/15
Loan
Keywords: Equilibrium (Economics); Oligopolies; Competition, Imperfect; Foreign exchange